The Effect of Job Involvement and Job Insecurity on Employee Performance with Organizational Commitment as an Intervening Variable at Company: Pengaruh Job Involvement dan Job Insecurity terhadap Kinerja Karyawasn dengan Komitmen Organisasi Sebagai Variabel Intervening pada Perusahaan - Zuhruf, Lady Classica; Andriani, Dewi (Universitas Muhammadiyah Sidoarjo, 2023)
This study entitled the effect of job involvement and job insecurity on employee performance with organizational commitment as an intervening variable at PT. Indoprima Gemilang Surabaya.This research is a type of quantitative research with hypothesis testing. The sample 90 employees. The analytical tool used in this reserach is path analysis technique with the help of SmartPLS sofware 3.0. This study uses primary data and secondary data, The result of this study prove that (1)there is a positive and significant relationship between job involvement and organizational commitment, (2) there is positive and significant relationship beetweenjob insecutrity and organizational commitment, (3) job involvement has a positive relationship and significant effect on employee performance, (4) job insecurity has a positive relationship and significantly affects employee performance, (5)there is a positive relationship and between organizational commitment to employee performance (6)job involvement has a positive relatinship which is positive and significantly affect employee performance mediated by organizational commitment, (7) job insecurity has a positive relationship and significantly affect employee performance mediated by organizational commitment.